Seroprevalence for vaccine-preventable diseases among Italian healthcare workers - Luca Coppeta; Iacopo D'Alessandro; Antonio Pietroiusti; Giuseppina Somma; Ottavia Balbi; Ilaria Iannuzzi; Andrea Magrini (Taylor & Francis Group, 2021)
Healthcare workers (HCWs) have an increased risk to be exposed to infectious diseases compared to the general population. For this reason, according to the National Immunization and Prevention Plan, all HCWs should have demonstrable evidence of immunity to measles, mumps, rubella, varicella and Hepatitis B. Earlier studies have already shown that a large percentage of Italian operators lacked immune protection for one or more of those pathogens. The aim of this study was to evaluate the immunization status for vaccine-preventable diseases of HCWs in a large Italian teaching hospital. We retrospectively evaluated clinical records and serological data of HCWs who followed the occupational health surveillance program between January 1 and December 31 2019. We reviewed the clinical records of 1,017 HCWs: 393 males and 624 females with a median age of 35.69 y (range: 19-67). Protective IgG antibody values were documented in the 88.0%, 75.7%, 90.3%, 87.4% and 85.7% of the HCWs screened, respectively, against measles, mumps, rubella, varicella and Hepatitis B. Age was significantly related to serological protection against measles, mumps and varicella but was not significantly related to protective IgG levels for rubella and HBV. Female gender was significantly related to a higher protection rate against Hepatitis B (87.8 vs 82.4%; p < .01) whereas males were significantly more protected against varicella (92-4 vs 84.1%; p < .01). Our study shows suboptimal levels of protection among Italian HCWs and a consequent increased risk of infection for them and their patients. Public health policies should be focused on improving preventive strategies, including serological screening and workplace vaccination of nonimmune individuals.